PERBANDINGAN PERUBAHAN DIMENSI HASIL CETAKAN ALGINAT PADA PENYIMPANAN KONDISI KERING DAN LEMBAB - , PRIMA DEWI KHRISTINA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Alginate impression material used to produce gypsum molds on a wide applications, including restorative, orthodontics, and the manufacture of removable prostheses. Alginate impression is very susceptible to dimensional changes due to water loss when it has to be stored. This study was conducted to compare the results the dimensional changes of alginate impressions in dry and humid storage conditions. This study used alginate impression material (Aroma Fine Plus, Japan). Eight samples of the alginate impressions in tray-shaped beam (7x7x4 cm) pressed into master cast cube (3x3x2 cm) divided in to 2 groups. Groups A alginate impressions placed in an open-air at room temperature 23±1°C with 65% humidity. Group B alginate impressions stored in the plastic box with damp paper towel inside so humidity in the box could reach 100%. Alginate impressions were stored within 2 hours and then filled with dental stone. Dental stone cast measured at length, height, tall using digital vernier caliper (Wipro, China) then calculated the volume. Dimensional change of the alginate impressions were difference volume of dental stone casts and the master cast. Data were analyzed using student t-test. Dimensional changes mean in dry conditions was 1184.59±74.66mm3 and for the humid conditions was 284.78±53.82mm3. The student t-test results showed significant dimensional change difference between those two storage conditions (p<0,05). The conclusion of this study was dimensional change of alginate impressions which stored in dry condition were larger than the ones which stored in humid conditions.